The Effect of Ventilation Mode in Anesthesia on Renal Mobility During Retrograde Intrarenal Surgery. Single-Blind Randomized Study - Dogan, Cagri; Akgül, Murat; Şahin, Ayhan; Yazıcı, Cenk Murat; Şahin, Mehmet Fatih; Altın, Enes; Keleş, Anıl (Urology Journal, 2023)
Purpose: Renal mobility can present challenges for surgeons during stone fragmentation. The respiratory setup of the mechanical ventilator during RIRS might affect renal mobility. The aim of this study was to evaluate the effect of high ventilation (HV) and standard ventilation (SV) modes on renal mobility during RIRS. Materials and Methods: Patients who underwent RIRS at a single center between November 2020 and November 2021 were retrospectively included in the study. Renal mobility was measured under fluoroscopic view in HVandSV modes during retrograde pyelography. The surgeon, who was absolutely blind about mechanical ventilation modes, was asked to assess the renal movement grade. After the ventilation mode was changed, the surgeon reassessed renal mobility. The data and the surgeon’s assessment were recorded and compared to each other. Results: A total of 86 patients with a mean age of 48.6 ± 15.7 years were included in the study. There was a significant difference between the SV and HV modes in terms of renal mobility in fluoroscopic view (17.1±6.1 mm and 13.6 ± 5.2mm, respectively; p=0.007). According to the surgeon’s assessments, the grade of renal mobility was found to be significantly higher in the SV group 2.8 ±1.1 compared to the HV group 2.2 ± 0.8 (p=0.001). Renal movement increased significantly under fluoroscopic vision as the renal grading of the surgeon increased(p=0.013). This data demonstrated that the surgeon’s assessment of renal mobility was significantly correlated with fluoroscopic kidney movement. Conclusion: Kidney movement was decreased significantly in HV mode during RIRS according to both fluoroscopic findings and surgeon assessment. Most surgeries of mobile kidneys were performed in HV mode, due to the surgeon’s preference.